ChemInform Abstract: Iminopyridine Oxazoline Iron Catalyst for Asymmetric Hydroboration of 1, 1‐Disubtituted Aryl Alkenes. Issue 22 (15th May 2015) - Chen, Jianhui; Xi, Tuo; Lu, Zhan
Abstract: Highly regio‐ and enantioselective anti‐Markovnikov hydroboration of 1, 1‐disubstituted aryl alkenes (I) is achieved using a novel chiral iminopyridine oxazoline ligand.